Pengaruh Rasio Profitabilitas dan Ukuran Perusahaan Terhadap Pertumbuhan Laba Pada Industri Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Agnesia, Tamara (Value : Journal of Management and Business, 2023)
The transportation and logistics industry is an industry that provides services in the form of transportation services and delivery of goods. The company's poor performance accompanied by the emergence of the covid-19 pandemic had an impact on the level of profit growth. The goal of this research was to examine the impact of profitability ratio and firm size on profit growth in trasnportastion and logistics businesses on the IDX from 2018 to 2021. This research generated 9 samples from 31 populations that fit the requirements using a sampling approach known as purposive sampling. The tests carried out were descriptive analysis and verification analysis assisted by instruments in the form of SPSS version 23 and Microsoft Excel as data processing tools. The results of testing the data show that the Profitability Ratio namely return on asset, has no partial effect on Profit Growth, while Firm Size has a partial effect on Profit Growth. Then simultaneously Profitability Ratios namely return on asset and firm size affect profit growth.